Modeling of pheratic aquifers on E, coli transport influenced by preconsolidation and compressibility of soil - Eluozo, solomon Ndubuisi (International Journal of Engineering and Technology, 2012)
The rate of pollution on soil are the major problem of ground water contamination in the study area, the influence from preconsolidation and compressibility of soil influence on E.coli transport has been carried out. This is to determine the rate of influence on E.coli transport in pheratic aquifers, mathematical model were developed to monitor the influence on the preconsolidation and compressibility of soil on microbial transports, experimental analysis were also carried out through a standard column experimental analysis, ten samples were collected in a drilling site at interval of three metres each for several location, the effluent discharge from the lower end of the column were collected and subjected to a thorough analysis, the theoretical values were compared with experimental values, and both values compared faviourably well. This study has explained the transport of E.coli base on the level of concentration generate from aquiferious zone. The study has reveal that the exploration of ground water should be design with its criteria’s to prevent the wild spread of water pollution emanating from the E.coli transport in the study areas, the preconsolidation and compressibility of soil were found to be insignificant on the transport of the microbes, the preconsolidation and its rate compressibility of soil could not reduce the transport of E.coli on a natural state.